2011
DOI: 10.1080/09602011.2010.547345
|View full text |Cite
|
Sign up to set email alerts
|

Rehabilitation of everyday memory deficits in paediatric brain injury: Self-instruction and diary training

Abstract: Memory problems that interfere with everyday living are frequently reported in children who have sustained acquired brain injury (ABI), but their nature and rehabilitation is under-researched. This study aimed to (1) determine neuropsychological correlates of everyday memory deficits in children with ABI, and (2) investigate the effectiveness of a newly developed programme for their rehabilitation. We assessed everyday memory, verbal memory, attention and behaviour in 15 children with ABI. The children attende… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(8 citation statements)
references
References 64 publications
0
8
0
Order By: Relevance
“…Second, we cautiously assume that the diary writing in the control group might have enhanced language-related connectivity after the intervention. Some studies also demonstrated the effects of diary training at the cognitive and behavioral levels (Ho et al, 2011; Travers, 2011). The fronto-temporal rsFC has been known for its role in the language network; in particular, decoupling between ACC-temporal gyrus connectivity is associated with auditory hallucinations in individuals with schizophrenia (Stamatakis et al, 2005).…”
Section: Discussionmentioning
confidence: 98%
“…Second, we cautiously assume that the diary writing in the control group might have enhanced language-related connectivity after the intervention. Some studies also demonstrated the effects of diary training at the cognitive and behavioral levels (Ho et al, 2011; Travers, 2011). The fronto-temporal rsFC has been known for its role in the language network; in particular, decoupling between ACC-temporal gyrus connectivity is associated with auditory hallucinations in individuals with schizophrenia (Stamatakis et al, 2005).…”
Section: Discussionmentioning
confidence: 98%
“…External aids with and without metacognition/strategy use External aids seemed mainly useful when the treatment goal is to improve specific daily life cognitive functions, such as everyday memory (67). External aids in combination with metacognition/strategy use have additional positive effects on some cognitive functions and limited areas of psychosocial functioning (68), again supporting the use of multi-component interventions. Given that only two studies investigated external aids either alone or in a multi-component intervention, results remain preliminary.…”
Section: Drill-based/computerized Interventions and The Effect Of Intmentioning
confidence: 98%
“…22 The WCQ has been widely used to explore parent coping. [23][24][25] Child Behavior Check List (CBCL), 26 a widely used tool, [27][28][29] measures parent perceptions of their child's problem behaviours. The CBCL consists of three categories of problems and a total score.…”
Section: Methodsmentioning
confidence: 99%